THE DETERMINANTS OF FINANCIAL PERFORMANCE IN GENERAL INSURANCE COMPANIES IN KENYA - Mirie Mwangi; Jane Wanjugu Murigu (European Scientific Journal, ESJ, 2015)
The contribution of the general insurance industry in Kenya to the gross domestic product is at 2.08%. This is low and hence the need to establish factors that can influence improved performance of some of the key players – the general insurance companies. The study was therefore to establish the factors that affect the profitability of general insurers in Kenya. The study employed multiple linear regression, with return on assets as the dependent variable, and considered all the general insurance companies in Kenya for the period 2009-2012. Profitabilitywas positively related to leverage, equity capital, management competence index and negatively related to sizeand ownership structure. The study did not find a relationship between performance and retention ratio, liquidity, underwriting risk and age. The study recommends that for general insurers in Kenya to perform better they should increase leverage, equity capital and quality of staff.